A Libras é legal: o papel da Federação Nacional de Educação e Integração dos Surdos no reconhecimento linguístico da Língua Brasileira de Sinais
This work, based on the theoretical perspective of Linguistic Historiography, aims to investigate the role of the Federação Nacional de Educação e Integração dos Surdos (FENEIS) in the process of language recognition of the Brazilian Sign Language. Fourteen reports on the institution's annual activities produced between 1987 and 2003 were selected and analyzed based on internal parameters - the conception of language and arguments for officialization - and external parameters - the climate of opinion at the time and the strategies used to disseminate Libras. The results indicate that the defense for the promotion of Libras was historically based on the perspective that its recognition was the only way to guarantee the deaf community's access to citizenship and their inclusion in society. There is also a strong criticism of the dominant ideology of the time, which understands the deafness from a medicalized perspective. Finally, among the numerous FENEIS strategies for the dissemination, consolidation and recognition of Libras, the initiatives of offering sign language courses and valuing the profession of the Libras interpreter stand out.